PERAN GURU DALAM MENGINTEGRASIKAN NILAI-NILAI KRISTIANI DALAM PEMBELAJARAN LIFE SKILL DI ERA PANDEMI COVID-19 - Tumbur Tinambunan; Frans Pantan; Johni Hardori (Edukasi : Jurnal Pendidikan Agama Kristen, 2021)
This research aims to identify effective strategies for teaching life skills based on Christian values ??during the Covid-19 pandemic. The pandemic has changed how learning is done, forcing teachers to innovate in delivering material online. This creates challenges in building supportive and inclusive learning environments and helping students manage psychological and emotional stress. The research method used is a literature study and document analysis to identify relevant strategies. The research results show that several effective strategies include building an inclusive learning environment online, adopting a student-centred learning approach, integrating emotional and mental well-being aspects in learning, adapting curriculum and methods, collaborating between schools, parents and communities, and utilizing technology effectively maximum. Hopefully, these findings can help teachers develop effective learning strategies in teaching life skills based on Christian values ??during the COVID-19 pandemic.